A Novel Homozygous CGA > TGA Mutation at Codon 123 (Exon 6) of B-Linker Protein (BLNK) as a Potential Cause of ‎Hepatopathy and Rickets: A Case Report - Kose, Hulya; Karali, Yasin; Kilic, Sara Sebnem (Iranian journal of immunology, 2025)
BLNK deficiency is a subtype of autosomal recessive immune disorders that involves a lack of B cells, agammaglobulinemia, and recurrent infections. We present the case of a 29-year-old Turkish female with BLNK deficiency caused by a novel homozygous CGA > TGA mutation at codon 123 (exon 6) in the BLNK gene. She developed severe liver failure and rickets at the age of 12. Although BLNK mutations are a rare cause of agammaglobulinemia, it is important to consider them in patients with B-cell deficiency and non-immune involvement.